If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -40 = 6x + 38 Reorder the terms: -40 + 12x = 6x + 38 Reorder the terms: -40 + 12x = 38 + 6x Solving -40 + 12x = 38 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -40 + 12x + -6x = 38 + 6x + -6x Combine like terms: 12x + -6x = 6x -40 + 6x = 38 + 6x + -6x Combine like terms: 6x + -6x = 0 -40 + 6x = 38 + 0 -40 + 6x = 38 Add '40' to each side of the equation. -40 + 40 + 6x = 38 + 40 Combine like terms: -40 + 40 = 0 0 + 6x = 38 + 40 6x = 38 + 40 Combine like terms: 38 + 40 = 78 6x = 78 Divide each side by '6'. x = 13 Simplifying x = 13
| 7m-9m=10 | | -1000+x^2=0 | | 4x-(5x+5)=2x-44 | | v(2)+2v+1=0 | | 6x-(4x+4)=6 | | x^2=1000 | | -12+9y=-6 | | Y=-5X^2+3X+8 | | 2z-4z=18 | | 186.83=2.54w+15.47 | | c=2.54(12.5)+15.47 | | c=2.54(19)+15.47 | | c=2.54(12)+15.47 | | c=2.54(2)+15.47 | | 3w^2+22w+7=0 | | -5+19=4b-8-3b | | 11=7+4x | | 3+-5=4(t+4) | | 8g-17=39 | | 12=5+3x | | 14t-3=81 | | -4(7a+2a)-5= | | 16=7+5b | | 3x+6y=0 | | 3-2x=10+5x | | 14=4x-14 | | 45+4(2n-15)=1 | | 5+(-12r)+8r= | | 4x-7=5x+7 | | 9-4r-7= | | 3x+1.5y=2850 | | (x-9)(2x-1)=0 |